(untitled) (Bangladesh Journal of Botany, 2023)
Partial nutritional analysis including total polyphenols, vitamin C, total soluble solids (°Brix), soluble sugars and mineral constituents was evaluated for the banana fruits derived from six triploid Musa accessions grown in coastal oasis of south of Tunisia. Results showed that pH values ranged from 5.44 to 6.01. The °Brix values varied between 4.00 g/100 g (Fresh weight) FW in ‘Arbi IRA’, and 1.33 g/100 g FW in ‘Lobnani’. Carbohydrates were quantified in all tested samples of the six accessions of banana fruits whereas sucrose was detected only in four accessions. The highest values of glucose, fructose and sucrose were 2.7, 3.37and 1.8 g/100 g FW, respectively. Total polyphenols content ranged from 46.0 to 55.08 mg GAE /100g FW. Vitamin C was detected in smaller quantity. Regarding the mineral composition K, P and Na were found in relatively large quantities in banana fruits whereas the levels of Mg and Ca were medium. Significant disparities were detected in mineral contents of banana samples. The micro-elements composition such as zinc, copper, iron and magnesium varied according to the tested accessions. The analysis showed a high Fe content of up to 1945 mg/100g dried matter. Therefore, banana fruits may be recommended for daily supplies of Fe, K and other mineral elements. Bangladesh J. Bot. 52(2): 253-260, 2023 (June)